Regular and App-Enhanced Maintenance of Physical Activity among Latinas: A Feasibility Study. Issue 1 (13th January 2022) - Mendoza-Vasconez, Andrea S.; Solis Becerra, Esther; Badii, Nathaniel; Crespo, Noe; Hurst, Samantha; Larsen, Britta; Marcus, Bess H.; Arredondo, Elva M.
Abstract : Supplemental digital content is available in the text. ABSTRACT: Introduction: Few studies have focused on physical activity (PA) maintenance, particularly among minority populations; smartphone apps could provide valuable tools. This study aimed to 1) assess and understand PA maintenance among Latinas who completed a PA intervention, and 2) evaluate the feasibility, acceptability, and preliminary efficacy of commercial smartphone apps as tools for PA maintenance. Methods: For this feasibility study, 27 Latinas who completed a PA intervention and increased their PA were randomly assigned to enhanced maintenance (i.e., taught to use commercial smartphone apps, n = 14) or regular maintenance (i.e., no additional treatment, n = 13). After 3 months, the feasibility and acceptability of using apps for PA maintenance was assessed via survey questions, analyzed using descriptive statistics. PA was reassessed via the 7-d PA recall and analyzed using longitudinal mixed effects regression models. Qualitative data were collected via open-ended interview questions and analyzed using thematic analysis. Results: Forty-three percent of enhanced maintenance participants reported using study apps at least "a little" and 21% using them "a lot." Although not statistically significant, enhanced maintenance participants reported a smaller drop in PA from postintervention to postmaintenance, compared with regular maintenance participants. Several participants expressed approval of the apps, whereas others reported on factors that kept them from using the apps for PA maintenance. Conclusions: Incorporating lessons learned from this study, larger randomized trials are warranted to evaluate the efficacy of using smartphone apps to support PA maintenance. The widespread use of apps could make them ideal tools to support PA maintenance after interventions in different settings.